Innovation Doesn’t Work: The Explanatory Power of a Socio-Technical Approach - Becerra, Lucas Dardo (2023)
This comment engages with two questions introduced by Alan Irwin’s introductory essay to this thematic collection on STS and Innovation (2023), and invites the reader to reflect on them as parts of a problemsolution relationship: When it comes to engaging with and acting upon socio-technical change, is ‘innovation’ part of the solution or of the problem? What new conceptual and empirical resources can STS bring to the study of innovation? The ‘problematic side’ (the first question) of our argument is focused on the theoretical constraints of ‘innovation’ as an analytical concept. Then, to address the ‘solution side’ (the second question), we introduce an approach to socio-technical change: the interactive socio-cognitive model. This model is presented as an analytical framework that makes explicit the explanatory (and programmatic) advantages that the notion of socio-technical change has compared to innovation.